Best selling coach : business development for business coaches, consultants and advisors - Bonnington, Rebecca; Davies, Nick (Routledge, 2025)
Written by a sister and brother team with 35 years of combined experience, this book demystifies business development and offers a simple and highly effective method of selling for business coaches and consultants.Selling professional services, particularly for new or aspiring consultants, can seem daunting and distasteful. This book shows that it doesn't need to be this way and, using a four-stage process, shows coaches how to first build their confidence and go on to locate, connect and meet desirable clients, virtually or in person. This book guides readers through asking for the sale and keeping control of the business relationship as it develops. Complete with email and letter templates and LinkedIn strategies, many chapters also link to an online course which gives access to downloadable materials such as professionally designed PDFs suitable for workshops, presentations and coaching sessions.Current, new and aspiring business coaches, as well as postgraduate coaching students, will welcome this guide to solving the top issues most people face in this sector: finding new clients, building your client base and winning work.
"Written by a sister and brother team with 35 years of combined experience, this book demystifies business development and offers a simple and highly effective method of selling for business coaches and consultants. Selling professional services, particularly for new or aspiring consultants, can seem daunting and distasteful. This book shows that it doesn't need to be this way, and using a four-step process, shows coaches how to first build their confidence, and go on to locate, connect and meet desirable clients, virtually or in-person. The book guides readers through asking for the sale and keeping control of the business relationship as it develops. Complete with email and letter templates and LinkedIn strategies, each chapter also links to an online course which gives access to downloadable materials such as professionally designed PDFs suitable for workshops, presentations and coaching sessions. Current, new and aspiring business coaches, as well as postgraduate coaching students, will welcome this guide to solving the top issues most people face in this sector: finding new clients, building your client base and winning work"-- Provided by publisher.
Keywords: Executive coaching.; Business consultants.; Marketing.; Small business -- Management.; elektronické knihy; electronic books